Cerebral–placental–uterine ratio as novel predictor of late fetal growth restriction: prospective cohort study. (4th September 2019) - MacDonald, T. M.; Hui, L.; Robinson, A. J.; Dane, K. M.; Middleton, A. L.; Tong, S.; Walker, S. P.
ABSTRACT: Objective: Fetal growth restriction (FGR) is a major risk factor for stillbirth and most commonly arises from uteroplacental insufficiency. Despite clinical examination and third‐trimester fetal biometry, cases of FGR often remain undetected antenatally. Placental insufficiency is known to be associated with altered blood flow resistance in maternal, placental and fetal vessels. The aim of this study was to evaluate the performance of individual and combined Doppler blood flow resistance measurements in the prediction of term small‐for‐gestational age and FGR. Methods: This was a prospective study of 347 nulliparous women with a singleton pregnancy at 36 weeks' gestation in which fetal growth and Doppler measurements were obtained. Pulsatility indices (PI) of the uterine arteries (UtA), umbilical artery (UA) and fetal vessels were analyzed, individually and in combination, for prediction of birth weight < 10 th, < 5 th and < 3 rd centiles. Doppler values were converted into centiles or multiples of the median (MoM) for gestational age. The sensitivities, positive and negative predictive values and odds ratios (OR) of the Doppler parameters for these birth weights at ∼ 90% specificity were assessed. Additionally, the correlations between Doppler measurements and other measures of placental insufficiency, namely fetal growth velocity and neonatal body fat measures, were analyzed. Results: The Doppler combination most strongly associated with placental insufficiency was a newly generated parameter, which we have named the cerebral–placental–uterine ratio (CPUR). CPUR is the cerebroplacental ratio (CPR) (middle cerebral artery PI/UA‐PI) divided by mean UtA‐PI. CPUR MoM detected FGR better than did mean UtA‐PI MoM or CPR MoM alone. At ∼ 90% specificity, low CPUR MoM had sensitivities of 50% for birth weight < 10 th centile, 68% for < 5 th centile and 89% for < 3 rd centile. The respective sensitivities of low CPR MoM were 26%, 37% and 44% and those of high UtA‐PI MoM were 34%, 47% and 67%. Low CPUR MoM was associated with birth weight < 10 th centile with an OR of 9.1, < 5 th centile with an OR of 17.3 and < 3 rd centile with an OR of 57.0 ( P < 0.0001 for all). CPUR MoM was also correlated most strongly with fetal growth velocity and neonatal body fat measures, as compared with CPR MoM or UtA‐PI MoM alone. Conclusions: In this cohort, a novel Doppler variable combination, the CPUR (CPR/UtA‐PI), had the strongest association with indicators of placental insufficiency. CPUR detected more cases of FGR than did any other Doppler parameter measured. If these results are replicated independently, this new parameter may lead to better identification of fetuses at increased risk of stillbirth that may benefit from obstetric intervention. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.